Enhanced enzymatic stability and antitumor activity of Daunorubicin-GnRH-III bioconjugates modified in position 4 - Manea, Marilena; Leurs, Ulrike; Orbán, Erika; Baranyai, Zsuzsa; Öhlschläger, Peter; Marquardt, Andreas; Schulcz, Ákos; Tejeda, Miguel; Kapuvári, Bence; Tóvári, József; Mező, Gábor (My University, 2011)
Here, we report on the synthesis, enzymatic stability, and antitumor activity of novel bioconjugates containing the chemotherapeutic agent daunorubicin attached through an oxime bond to various gonadotropin-releasing hormone-III (GnRH-III) derivatives. In order to increase the enzymatic stability of the bioconjugates (in particular against chymotrypsin), 4Ser was replaced by N-Me-Ser or Lys(Ac). A compound in which 4Lys was not acetylated was also prepared, with the aim of investigating the influence of the free ε-amino group on the biochemical properties. The in vitro cytostatic effect of the bioconjugates was determined on MCF-7 human breast, HT-29 human colon, and LNCaP human prostate cancer cells by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Their stability/degradation (1) in human serum, (2) in the presence of rat liver lysosomal homogenate, and (3) in the presence of digestive enzymes (trypsin, chymotrypsin, and pepsin) was analyzed by liquid chromatography in combination with mass spectrometry. The results showed that (1) all synthesized bioconjugates had in vitro cytostatic effect, (2) they were stable in human serum at least for 24 h, and (3) they were hydrolyzed in the presence of lysosomal homogenate. All compounds were stable in the presence of (1) pepsin and (2) trypsin (except for the 4Lys containing bioconjugate). In the presence of chymotrypsin, all bioconjugates were digested; the degradation rate strongly depending on their structure. The bioconjugates in which 4Ser was replaced by N-Me-Ser or Lys(Ac) had the highest enzymatic stability, making them potential candidates for oral administration. In vivo tumor growth inhibitory effect of two selected bioconjugates was evaluated on orthotopically developed C26 murine colon carcinoma bearing mice. The results indicated that the compound containing Lys(Ac) in position 4 had significantly higher antitumor activity than the parent bioconjugate.
Keywords: 540